2018
DOI: 10.3847/1538-4357/aae079
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic Modeling of a Solar Eruption Associated with an X9.3 Flare Observed in the Active Region 12673

Abstract: On SOL2017-09-06 solar active region 12673 produced an X9.3 flare which is regarded as largest to occur in solar cycle 24. In this work we have preformed a magnetohydrodynamic (MHD) simulation in order to reveal the three-dimensional (3D) dynamics of the magnetic fields associated with the X9.3 solar flare. We first performed an extrapolation of the 3D magnetic field based on the observed photospheric magnetic field prior to the flare and then used it as the initial condition for an MHD simulation. Consequentl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 68 publications
9
63
0
Order By: Relevance
“…We suggest that the recent 3D data driven studies of eruptive phenomena, based on the initialization of resistive 3D MHD codes with Non-Linear Force Free Extrapolations of the observed magnetograms of specific active regions, driven by the turbulent photospheric activity [55,99,113], is clearly closer to reality.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We suggest that the recent 3D data driven studies of eruptive phenomena, based on the initialization of resistive 3D MHD codes with Non-Linear Force Free Extrapolations of the observed magnetograms of specific active regions, driven by the turbulent photospheric activity [55,99,113], is clearly closer to reality.…”
Section: Discussionmentioning
confidence: 70%
“…It is important to connect the sketch in Fig. 3 with the evolution of eruptive magnetic Inoue et al [55] performed a magnetohydrodynamic (MHD) simulation in order to reveal the three-dimensional dynamics of the magnetic fields associated with a X9.3 solar flare. They first performed an extrapolation of the 3D magnetic field based on the observed photospheric magnetic field prior to the flare and then used this as the initial condition for the MHD simulation, which revealed a dramatic eruption, see Fig.…”
Section: The Evolution Of Magnetic Topologies and Eruptive Phenomenamentioning
confidence: 99%
“…These studies thus emphasise the complex evolution of this AR and most of them feature several flux rope systems. In addition, Inoue et al (2018) found, using an MHD simulation initiated by NLFFF reconstruction, that the eruption of these flares initially included several small flux ropes and that magnetic reconnection played an important role. Similarly, Jiang et al (2018) presented a detailed study of the magnetic topology surrounding the X9.3 flare using an NLFFF initiated MHD simulation.…”
Section: Introductionmentioning
confidence: 99%
“…This active region and its eruptions have been the subject of a number of studies (e.g. Yang et al 2017;Chertok et al 2018;Hou et al 2018;Inoue et al 2018;Liu et al 2018;Verma 2018;Yan et al 2018;Morosan et al 2019;Romano et al 2019;Zou et al 2019). During its transit across the solar disc, this AR produced four GOES X-class flares and numerous weaker flares.…”
Section: Introductionmentioning
confidence: 99%
“…Flare activity was also discovered on the solar-type stars other than the Sun (Schaefer et al 2000;Benz & Güdel 2010;Shibata & Magara 2011;Maehara et al 2012;Notsu et al 2013;Shibayama et al 2013;Balona 2015;Davenport 2016). Solar flares commonly come from solar active regions (ARs), and the magnetic configuration of flare-bearing ARs is one key aspect for understanding the initiation and evolution of solar flares (e.g., Chen et al 2012;Sun et al 2015;Jiang et al 2016Jiang et al , 2018Liu et al 2016;Cheng et al 2017;Guo et al 2017;Hao et al 2017;Inoue et al 2018) and other related eruptive phenomena in the solar atmosphere (e.g., Zhang et al 2012;Ouyang et al 2017;Wang et al 2017;Liu et al 2018). The non-potential property of the magnetic fields with electric current permeating inside is believed to be the critical aspect related to the activity level of ARs (e.g., Wang et al 1996;Leka & Barnes 2003;Schrijver 2016).…”
Section: Introductionmentioning
confidence: 99%